# What is the average rate of change of f(x) = -2x + 1 from x = -5 to x = 1

-10, -2, -5, 10

**Solution:**

The average rate of a function f(x) between a and b is defined as [f(b) - f(a)]/(b - a)

According to the question,

The average rate of change of a function f(x) between -5 and 1 is

[f(-5) - f(-1)]/ (-5 - 1)

Evaluate f(-5) and f(1)

f(-5) = -2(-5) + 1 = 10 + 1 = 11

f(1) = -2(1) + 1 = -2 + 1 = -1

By substituting the values we get,

[f(-5) - f(-1)]/ (-5 - 1) = (11 + 1)/(-5 - 1) = 12/-6 = -2

Therefore, the average rate of change of f(x) = -2x + 1 from x = -5 to x = 1 is -2.

## What is the average rate of change of f(x) = -2x + 1 from x = -5 to x = 1?

**Summary:**

The average rate of change of f(x) = -2x + 1 from x = -5 to x = 1 is -2.